Efficiency Improvement in Production Using MRP Method at Kerupuk Udang Kelapa Company - Farchan, Fauzi; Tiara Fitri Rizkiyah; Azzatillah, Azzatillah; Annisa, Annisa (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to enhance production efficiency at Kerupuk Udang Kelapa Indramayu by implementing the Material Requirements Planning (MRP) method combined with the Economic Order Quantity (EOQ) approach and forecasting techniques. The forecasting method employed is Least Squares to predict raw material needs. The findings reveal that the previous inventory management was suboptimal, with an efficiency level of 0.9710 in 2023. After implementing the MRP method, efficiency improved to 1.0, reflecting optimal production efficiency. This result demonstrates that integrating MRP, EOQ, and forecasting optimizes raw material inventory and enhances Kerupuk Udang Kelapa production efficiency.